Aerobic capacity and fatigability are associated with activity levels in women with hip osteoarthritis. Issue 6 (21st September 2020) - Foucher, Kharma C.; Aydemir, Burcu; Huang, Chun‐Hao; Horras, Megan; Chmell, Samuel J.
Abstract: Physical activity is important for physical function and pain relief in people with lower extremity osteoarthritis (OA). Unfortunately, people with OA are not as active as their peers without OA. The objective of this study was to determine whether aerobic capacity and fatigability are associated with physical activity in women with hip OA. We conducted a cross‐sectional analysis of 36 women with hip OA. We assessed aerobic fitness as predicted VO2 max from a 6‐min walk test. We assessed fatigability using a treadmill test. Finally, we assessed self‐reported physical activity using the UCLA activity scale and quantified steps per day and activity intensity using accelerometers. We used Pearson correlations to determine associations. We used regression analysis to determine whether fatigability mediated the association between aerobic fitness and physical activity. On average, subjects were moderately active via the UCLA score (5.2 ± 1.3 out of 10). Aerobic fitness ( R  = 0.582, p  < .001) and fatigability ( R  = 0.516, p  =.003) were significantly correlated with UCLA scores. However, aerobic fitness was the best predictor of UCLA scores, as well as sedentary time,  and time spent in light activity. Fatigability was not a mediator between aerobic fitness and UCLA scores. Aerobic fitness and fatigability may be modifiable barriers to physical activity in people with OA. Future interventional studies should examine whether improving aerobic fitness improves physical activity or fatigability.